The Dynamics of Islam and State Relations in Indonesia - Adelia Luthfiana Azizah, Reza; Mubaraq, Zulfi; Mustofa, M. Lutfi; Toriquddin, Moh. (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The study of the relationship between Islam and the State is of significant academic importance and warrants further exploration. The debate surrounding this topic remains ongoing. This paper seeks to address three key aspects: First, the paradigms of Islam-State interrelations. Second, the internal and external factors influencing the relationship between Islam and the State. Third, the positive and negative implications of this interrelationship on state governance and societal structures. This research employs a literature review method with a descriptive qualitative approach, analyzed through content analysis techniques. The findings reveal three key points. The study identifies three paradigms: (1) Secularistic, (2) Integralistic, and (3) Symbiotic Mutualistic. Internally, the interrelation is shaped by: (1) The social structure of Indonesian society, (2) The ideological perspectives of Indonesian political leaders, (3) The history of Indonesian independence, and (4) The religiosity of the Indonesian populace. Externally, it is influenced by: (1) The ideological positions of foreign political leaders, (2) Foreign policies, and (3) Islamic-based state ideologies. The implications for society and state governance are both positive and negative. On the positive side: (1) A compromise between secular and integral paradigms contributes to societal harmony in Indonesia, (2) Human rights, particularly in the domains of religion and state, are respected, and (3) Amendments and changes to state statutes and laws are made in alignment with the evolving conditions of Indonesian society. On the negative side: (1) Disputes over the fundamental ideology of the Indonesian state persist, (2) Divisions in understanding based on differing paradigms are evident, and (3) There is a growing fanaticism associated with these ideological paradigms. In conclusion, the paper argues that the symbiotic mutualistic paradigm governing the relationship between Islam and the State is both valid and relevant to the social conditions in Indonesia.